Descriptive study of the youth male judoka aged 10-14 years by competitive age group and maturity status - Giudicelli, B. (Revista de Artes Marciales Asiaticas, 2016)
Adolescences, due to the growth and maturation, experience increments in body size, in body composition, in functional capacity and in motor dexterity (Malina, Bouchard, & Bar-Or, 2004), and these changes have a major impact on the physical performances. It is common during this period we find young athletes of the same age and sports category at different levels of growth and maturation, which may result in inequities related to body size and functional capabilities (Malina, et al., 2010). In combat sports, specifically in judo, where performance can be determine by physical, technical, tactical and psychological abilities (Detanico, Dal Pupo, Franchini, & Giovana dos Santos, 2012), with extensive physical contact, it becomes even more pertinent to assess how the processes of growth and maturation affect the performance of young athletes in order to instrument the physical education teachers and coaches with relevant pedagogical and methodological training information, in order to protect these athletes, to gain in physical and sports performance and to contribute to the practice for the long term.